The effect of technical training on physical parameters of 11-14 years old freestyle wrestlers - Faruk Güven (Turkish Journal of Kinesiology, 2023)
This study aims to determine the physical changes resulting from technical training applied to adolescent wrestlers. Twenty-four male wrestlers volunteered to participate in the study. Participants were randomly divided into two groups: Experimental group (EG, n=14) and Control group (CG, n=14). The EG had a mean age of 12.54±0.82 years, a mean body weight of 48.36±8.23 kg, and a mean height of 156.18±8.58 cm. The CG had a mean age of 13.62±0.33 years, a mean body weight of 47.43±6.65 kg, and a mean height of 158.24±2.26 cm. The EG performed a 12-week technical training specific to freestyle wrestling while the CG continouned their regular wrestling training. Before and after the 12 week training period, skinfold thickness and body circumference measurements were carried out. There were significant differences between pre and post tests in subscapula, biceps, triceps, pectoral, abdominal, suprailiac, abdominal, suprailiac, and tight (p